5(m-2)+36=(-4)

Simple and best practice solution for 5(m-2)+36=(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m-2)+36=(-4) equation:


Simplifying
5(m + -2) + 36 = (-4)

Reorder the terms:
5(-2 + m) + 36 = (-4)
(-2 * 5 + m * 5) + 36 = (-4)
(-10 + 5m) + 36 = (-4)

Reorder the terms:
-10 + 36 + 5m = (-4)

Combine like terms: -10 + 36 = 26
26 + 5m = (-4)
26 + 5m = -4

Solving
26 + 5m = -4

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 5m = -4 + -26

Combine like terms: 26 + -26 = 0
0 + 5m = -4 + -26
5m = -4 + -26

Combine like terms: -4 + -26 = -30
5m = -30

Divide each side by '5'.
m = -6

Simplifying
m = -6

See similar equations:

| 2x+8=89 | | 0.83x=30 | | 2a^2-4a+3=0 | | 0=w^2-14w+38 | | 4x+18=6x-8 | | 6v^2-13v=28 | | -3=2x+x | | 7x+11=3n-17 | | 4x-6=3x+10 | | (2x+5)(3x-10)= | | 30(48x+12)=16x+-60 | | s^2+3s=0 | | 7x+12=9x-6 | | x^2+20=-9 | | 8x-4=6x+14 | | 6x-2=4x+4 | | -12x+9+24x+4=43 | | 0=-3y^2+7y+6 | | x-1=8x-8 | | 3(-2x+4)+5(4x-3)=4(-5x-2) | | 9x-3=4x-1 | | 7x-5=4x+7 | | =0.1428571429m+-0.4285714286y | | -(5y+5)-(-4y-7)=-1 | | 4(3x-7)-5(4x-2)= | | 7x+7=9x-9 | | 23x+67=55x-40 | | x^2+4x+6=10 | | 54*4= | | x+57,x=3 | | 4.39(5)+3.42N=76.11 | | 8x+2=7(x-4)+8 |

Equations solver categories